2013
DOI: 10.1254/jphs.13072fp
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Demethylation Treatment on Cigarette Smoke Extract–Induced Mouse Emphysema Model

Abstract: Abstract. In the present study, we explored the effects of demethylation in a cigarette smoke extract (CSE)-induced mouse emphysema model. Animals were randomly assigned to the control group, CSE group, 5-aza-2′-deoxycytidine (AZA) group, and CSE+AZA group (n = 10 per group). The mitochondrial transcription factor A (mtTFA) promoter methylation increased over 4-fold in the CSE group compared with the control group, which was reversed by AZA. The mtTFA and the cytochrome c oxidase subunit II (COX II) mRNA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 22 publications
9
27
0
Order By: Relevance
“…It is an inhibitor of DNA methyltransferase, which triggers demethylation, leading to changes in gene reactivation [16], sparking interest in its use as a potential therapeutic agent. It has been demonstrated that the demethylation treatment can protect against CSE-induced emphysema in an animal model [14,15]. In our study, the dysfunction of EPCs, decreased expression of eNOS, and increased expression of p16(INK4a) caused by CSE could be partly reversed by Dec.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is an inhibitor of DNA methyltransferase, which triggers demethylation, leading to changes in gene reactivation [16], sparking interest in its use as a potential therapeutic agent. It has been demonstrated that the demethylation treatment can protect against CSE-induced emphysema in an animal model [14,15]. In our study, the dysfunction of EPCs, decreased expression of eNOS, and increased expression of p16(INK4a) caused by CSE could be partly reversed by Dec.…”
Section: Discussionsupporting
confidence: 59%
“…It has been demonstrated that a demethylation agent can alleviate emphysema in an animal model [14,15]. Decitabine (Dec) is the most widely used agent of demethylation; it triggers demethylation, leading to a consecutive reactivation of epigenetically silenced genes in vitro and in vivo [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research 21,24 and this research found that CSE injection lead emphysematous change and abnormality of pulmonary function. Cigarette smoke was inhaled into the lung and diffused into the mucus and the blood as liquor phase.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, several nongenotoxic chemicals have been found to affect gene function through changes in DNA methylation (27). For example, the nongenotoxic rodent carcinogen phenobarbital induces global hypomethylation and regional hypermethylation in rodent livers (28,3,29).…”
Section: Introductionmentioning
confidence: 99%